Oral vancomycin use and incidence of vancomycin-resistant enterococci: time-series analysis - Seongman Bae; Kyungkeun Cho; Inah Park; Jiae Kim; Hyewon Han; Jiwon Jung; Sung-Han Kim; Sang-Oh Lee (Antimicrobial Resistance and Infection Control)
Summary Background Vancomycin exposure is a major risk factor for vancomycin-resistant enterococci (VRE) colonisation, but the relationship between oral vancomycin and the risk of VRE colonisation remains poorly understood without ecological evidence. In this study, we investigated the association between oral vancomycin usage and the incidence of hospital-acquired VRE using a time-series analysis. Methods This retrospective ecological study analysed monthly data on antibiotic usage and VRE incidence from January 2013 to December 2022 at a 2700-bed hospital in South Korea. Antibiotic usage was measured in days of therapy (DOT) per 1000 patient-days. Hospital-acquired VRE incidence was defined as the number of VRE isolates identified more than 48 h after admission per 1000 patient-days. The association between oral vancomycin use and VRE incidence was assessed using a multivariate autoregressive integrated moving average (ARIMA) regression model incorporating lag structures. Results Over 10 years, 5,763 clinical VRE isolates were identified, with 5,133 (89%) being hospital-acquired. Oral vancomycin usage and VRE incidence showed significant upward trends during the study period. In the final ARIMA model adjusting for various types of antibiotic use and baseline VRE carriage rate, a significant association was observed between oral vancomycin use and VRE incidence (coefficient: 0.0160, 95% CI: 0.0030 to 0.0290, P = 0.0162), with an R-squared value of 0.76. Sensitivity analyses demonstrated the robustness of the association between oral vancomycin use and VRE acquisition across various time lags between antibiotic use and VRE incidence. Conclusions There was a significant association between institutional oral vancomycin use and hospital-acquired VRE incidence, highlighting the need for antibiotic stewardship for oral vancomycin use to contain the nosocomial spread of VRE in addition to infection control measures.